An Efficient FPGA Implementation Of Multifunction Residue Architectures (International Journal of Engineering and Computer Science, 2018)
A design methodology for incorporating Residue Number System (RNS) and Polynomial Residue Number System (PRNS) in Montgomery modular multiplication in GF(p) or GF(2n) respectively, as well as a VLSI architecture of a dual-field residue arithmetic Montgomery multiplier are presented in this paper. An analysis of input/output conversions to/from residue representation, along with the proposed residue Montgomery multiplication algorithm, reveals common multiply-accumulate data paths both between the converters and between the two residue representations. A versatile architecture is derived that supports all operations of Montgomery multiplication in GF(p)  and GF(2n), input/output conversions, Mixed Radix Conversion (MRC) for integers and polynomials, dual-field modular exponentiation and inversion in the same hardware. Detailed comparisons with state-of-the-art implementations prove the potential of residue arithmetic exploitation in dual-field modular multiplication